Early detection of Austistic Spectrum Disorder in times of COVID-19 - Huete-Córdova, María (2021)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder, of multifactorial etiology, characterized by deterioration in social interaction, verbal and non-verbal communication, and restricted and repetitive patterns of behavior and interests that persists throughout life, presenting from mild modifications to severe disabilities. A review is made of the autism spectrum disorder in relation to early detection and the difficulties that have arisen in this vulnerable population group in this time of the COVID-19 pandemic.